Jerome Seymou (Journal of Parents and Teachers, 2012)
In this number of Grandes de la Educacion, the author talks about Jerome Seymour Bruner, a well-known psychologist of Harvard specialised on human cognitive psychology and cognitive learning theory in educational psychology. Bruner is very important person in the area of education.
Keywords: Psychology; cognitive psychology; cognitive learning theory; history of education; education.